2022
DOI: 10.1108/shr-08-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Employee experience: the new employee value proposition

Abstract: Purpose Knowing what employees expect in the never normal environment post-COVID-19 can help organizations understand talent needs and preferences – including how and where they want to work, as well as what they need to feel productive – and then initiate action on those expectations. So, this paper aims to delineate the factors that makes an employee experience (EX) that align, empower and accelerate business impact. Design/methodology/approach This viewpoint paper draws on extant literature review – acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Tangible stimuli include the physical environment (Batat, 2022) and technologies (Malik et al, 2023) Intangible stimuli include the work itself (i.e. job tasks), workplace culture, HR practices and leadership (Panneerselvam and Balaraman, 2022) as well as how the work fits in the employee's life (e.g. alignment between the employee's goals and those of the organization, work-life balance) (Pangallo et al, 2022) An employee empowered "state of mind" emerging from highinvolvement work practices may drive EX (Bowen, 2024) 3.…”
Section: Ex Stimulimentioning
confidence: 99%
“…Tangible stimuli include the physical environment (Batat, 2022) and technologies (Malik et al, 2023) Intangible stimuli include the work itself (i.e. job tasks), workplace culture, HR practices and leadership (Panneerselvam and Balaraman, 2022) as well as how the work fits in the employee's life (e.g. alignment between the employee's goals and those of the organization, work-life balance) (Pangallo et al, 2022) An employee empowered "state of mind" emerging from highinvolvement work practices may drive EX (Bowen, 2024) 3.…”
Section: Ex Stimulimentioning
confidence: 99%
“…EXM involves collecting and analyzing data on employees’ needs, expectations and experiences to identify the areas of improvement and offer personalized support to employees. This approach represents a shift away from traditional employee engagement management, focusing instead on the employee as a whole (Panneerselvam and Balaraman, 2022; Tucker, 2020).…”
Section: Employee Experience Managementmentioning
confidence: 99%
“…EX refers to employee psychocognitive sentiments toward their job that includes the cumulative impact of interactions with peers, organizational culture, leadership and overall work environment. Studies have shown that a positive EX can enhance employee satisfaction, engagement and retention, thereby improving organizational performance (Farndale and Kelliher, 2013; Panneerselvam and Balaraman, 2022). Therefore, prioritizing and improving EX is paramount to organizational success (Lemon, 2019; Malik et al , 2023; Maylett and Wride, 2017; Moganadas and Goh, 2022; Plaskoff, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Positive job experience provides cohesiveness, vigour, well-being, achievement, inclusiveness and a physical environment (Yadav & Vihari, 2021). Panneerselvam and Balaraman (2022) defined employee experience as the function of work, workplace culture, empowering technologies, flexible human resource and practices, and, importantly, inclusive leadership. However, impressive monetary benefits have long passed the criteria for luring employees to do their best at work (Plaskoff, 2017); if not, how come, after a humungous rise in compensations and rewards, employees are still less motivated, disengaged and unhappy at the workplace.…”
Section: Employee Engagement and Employee Experiencementioning
confidence: 99%